LEARNING STYLES OF SMAN 1 LAREH SAGO HALABAN STUDENTS AS THE BASIS FOR DEVELOPING EDUPARK TEACHING MATERIALS - Cahyani, Mauliditia Regita (Department of Physics Universitas Negeri Padang, 2025)
Understanding the learning styles of learners can create a supportive environment so that learners can more easily absorb information optimally. This research aims to analyze the learning styles of students at SMAN 1 Lareh Sago Halaban with the hope that the results of the analysis can be used as a basis for developing edupark teaching materials that suit the needs of students. This type of research is descriptive analysis. This research was conducted at SMAN 1 Lareh Sago Halaban involving 56 students. Data were collected using a questionnaire designed based on the learning style model. The results obtained prove that students have varied learning styles, but are more inclined to visual learning styles, namely 55% of students. Some learners find it easier to understand material that involves hearing and movement. By recognizing the different learning styles of learners, edupark teaching materials can be developed according to various needs and improve learning effectiveness.